Ophthalmic artery angioplasty for age-related macular degeneration. (5th January 2022) - Lylyk, Ivan; Bleise, Carlos; Lylyk, Pedro N; Perez, Nicolas; Lundquist, Javier; Scrivano, Esteban; Francone, Anibal A; Charles, Martin; Zompa, Tamara; Lylyk, Pedro
Abstract : Background: There is considerable overlap of contributors to cardiovascular disease and the development of age-related macular degeneration (AMD). Compromised ocular microcirculation due to aging and vascular disease contribute to retinal dysfunction and vision loss. Decreased choroidal perfusion is evident in eyes with dry AMD and is thought to play a role in retinal pigment epithelial dysfunction, the rate of development of geographic atrophy, and the development of neovascularization. The aim of the study was to demonstrate that AMD is correlated with a compromised blood flow in the ocular pathway and show OA angioplasty as a potential treatment of late-stage AMD. Methods: Based on the potential for the ophthalmic artery (OA) to be an anatomical target for the treatment of AMD as outlined above, five patients were found to be eligible for compassionate use treatment, presenting clinically significant late-stage AMD with profound vision loss in one or both eyes, and are included in this retrospective study. Results: OA narrowing, or significant calcium burden at the ophthalmic segment of the internal carotid artery compromising the origin of the OA was confirmed in all cases. Subsequent OA cannulation was achieved in all patients with some difficulty. Subjective patient reports indicated that all patients perceived a benefit following the procedure; however, improved postoperative visual acuity did not confirm that perceived benefit for one of the patients. Conclusions: Feasibility and safety of the OA angioplasty were demonstrated, and a benefit perceived in five patients with profound vision loss and a desire to achieve improved quality of life. A clinical trial with controlled schedule, imaging, and methodologies is needed to confirm these results.